(untitled) (Research, Society and Development, 2020)
This study evaluated the effects of gamma radiation treatment on the profile of phenolic compounds and the quality parameters of strawberries irradiated during storage. The fruits were submitted to irradiation doses 0, 0.8; 1.6, and 2.4 kGy and stored for up to 9 days at 10°C. The levels of anthocyanins, ascorbic acid, and total phenolic compounds were evaluated, as along with the profile of these compounds and colorimetric and microbiological parameters. Our results show that the doses used preserved the studied phenolic compounds. The variation in ascorbic acid values may be due to post-harvest storage of fruits. The applied doses did not interfere in the characteristic red color of the strawberry. The irradiation dose of 2.4 kGy more efficiently controlled microorganisms and is the ideal dose to increase the shelf life of strawberries.